P79 The importance of the physical environment in creating a social environment for adolescents and young adults in hospital. (18th November 2019) - Lea, S; Taylor, RM; Gibson, F
Abstract : Aim: There has been a welcome trend toward seperate services for young people. This has been in direct response to young people consistently calling for dedicated hospital services for their age group. Despite this trend, specialist cancer units for adolescents and young adults (AYA) only provide care for approximately half of AYA in England, the rest being cared for in child or adult environments. Previous research has described the importance of the environment on experiences of cancer care but this has centred mainly on specialist units only. It is unknown whether this is the same or different for all places of care. This study explored the impact of the physcial healthcare environment on young people and professionals' social experiences of care and care delivery. Methods: A multiple-case study was conducted in 24 hospitals in England between 2014 and 2015. It included: semi-structured interviews with AYA (n=29) and healthcare professionals (n=41); and observations (total=120hrs). Thematic analysis was used to analyse transcripts and field notes. Results: Three key themes were apparent in the data relating to the environment: the physical environment; the social environment; and the relationship between the two. The provision of a physical space for socialising was seen to be vital as it enabled AYA to come together, engage in peer support opportunities, socialise with existing peers, and to spend time with their family away from their hospital bed. Although fun, bright décor was described as beneficial, the positive impact of the social space had greater significance. The majority of those in child and adult-focussed care environments reported poor experiences of social interaction when in hospital. Conclusions: Poor experiences of AYA receiving care in adult care settings has been identified in previous research. The findings in this present study have compared these experiences against care received in bespoke AYA care settings: advocating for the provision of dedicated spaces which bring young people together. Services must be skilfully developed to create optimal spaces to deliver holistic, age-appropriate care. This will assist the structure, design and commissioning of AYA health services that are fit for purpose.